THE ROLE OF THE PSYCHOLOGIST IN POSTVENTION AND THE GRIEVING PROCESS OF ADOLESCENT SUICIDE IN A SCHOOL SETTING (Editora Impacto Científico, 2025)
This study explores the crucial role of psychologists in postvention and grief process following a suicide in school environments, particularly among adolescents. The loss by suicide is a multifaceted and intensely painful experience, often leading to complicated grief for survivors, including family members, friends, and educators. Given the alarming rates of suicide and self-harm among young people in Brazil, schools emerge as strategic settings for interventions. Psychologists play an indispensable role in offering psychoeducation, creating safe spaces for dialogue, promoting emotional processing of complex feelings, and strengthening support networks. The study highlights the need for continuous and sensitive interventions, involving family and peer support groups, to transform schools into environments of acceptance and resilience. Integrating mental health promotion into the school curriculum is essential to deconstruct stigmas and value life.DOI: https://doi.org/10.56238/edimpacto2025.090-071